Igrovye aspekty russkogo avangarda - Benčić, Živa (Array, 2000)
An attempt is made to answer the question whether the literature of the Russian avant-garde may be identified with play, if play stands for an activity which exists for its own purpose, which is autonomous, freed from the interests and norms of everyday life and unambiguosly separated from the sphere of work. The answer to this question can be affirmative only in the case of the early Russian avant-garde, which was not burdened with the problem of its own social utility and its participation in the social processes in general. As an activity which resided within its own confines, following its own, arbitrarily established rules, as an activity which inside the limits of its autonomy freely experimented with all the concealed possibilities of the artistic expression it indeed resembled play. However, following 1917, the avant-garde stopped looking for its aims within itself but found them in serving the new order, thus erasing its own internal room for play. As a result, it could perceive and intellectually organize itself only in terms of duty and work.